The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1007/bf01783627
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and disposition of inorganic arsenic in laboratory animals and humans

Abstract: The carcinogenicity of inorganic arsenic in humans, particularly in the lung and skin, has been reasonably well established through epidemiological investigations. However, there is no substantial experimental evidence for carcinogenicity in animals to support the human studies. Studies of metabolism and disposition of inorganic arsenic in various animal species are particularly relevant to determining the factors that might account for the lack of an animal model. Numerous studies of this type have been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Inorganic arsenic is reported to bind to the α-chain of hemoglobin and thereby accumulates in the RBCs. 20 Recently, we have also observed changes in RBC morphology in SA-exposed mice 4 that might cause destruction of RBC leading to development of anemia. 21 All these findings may support the fact of decreased hemoglobin level obtained in the present study.…”
Section: Discusisonmentioning
confidence: 91%
See 1 more Smart Citation
“…Inorganic arsenic is reported to bind to the α-chain of hemoglobin and thereby accumulates in the RBCs. 20 Recently, we have also observed changes in RBC morphology in SA-exposed mice 4 that might cause destruction of RBC leading to development of anemia. 21 All these findings may support the fact of decreased hemoglobin level obtained in the present study.…”
Section: Discusisonmentioning
confidence: 91%
“…[1][2][3] Ingested inorganic arsenic is readily absorbed through the gastrointestinal tract and distributed in various tissues through blood circulation. 4 This arsenic eventually causes growth retardation, blood cells distortion and elevation of various serum enzymes like lactate dehydrogenase (LDH), alkaline phosphatase (ALP), serum glutamic pyruvic transaminase (SGPT) etc. in human and rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that GSH elevation is a natural reaction to arsenic attack which probably acts as a protective mechanism (McKinney, 1992;Mazumder et al, 1988). The situation becomes more critical when the availability of free thiol group is low (malnutrition/protein deficiency) and enhanced expression of toxicity can occur.…”
Section: Community Health Effectsmentioning
confidence: 99%
“…Arsenic is then methylated to methylarsonic acid (MMA) and dimethylarsinic acid (DMA) (McKinney, 1992), and Sadenosylmethionine (SAM) has been shown to be the primary methyl donor in the arsenic transmethylation reactions (Vahter, 2002).…”
Section: Introductionmentioning
confidence: 99%